Struktur dan Sifat Dielektrik Senyawa Aurivillius CaBi3LaTi4O15 yang Disintesis dengan Teknik Hidrotermal - Zulhadjri Zulhadjri; Firmanul Qadri Amir; Marsal Mahmud; Upita Septiani; Syukri Arief (Universitas Andalas, 2020)
Synthesis of four-layer Aurivillius CaBi3LaTi4O15 has been successfully carried out by hydrothermal technique using NaOH 4 M as mineralizer. The reaction was carried out at 220 Â°C for 72 h. Crystal structure, morphology, and dielectric properties were analyzed in this study. X-ray diffraction confirmed that the single-phase product was successfully obtained. The refinement result shows the product has orthorhombic crystal structure with space group A21am. The morphology analyzed using SEM shows plate-like grains are observed, which is characteristic of Aurivillius phase. Dielectric curves show peaks at 585 Â°C which indicate ferroelectric transition temperature.